PERSPEKTIF GURU MADRASAH IBTIDAIYAH TERHADAP PENDIDIKAN BERBASIS AKHLAK DAN PERAN LINGKUNGAN PENDIDIKAN DALAM MENDUKUNG PROSES PEMBELAJARAN - Medi Yulison Arza; Achmad Junaedi Sitika; Agus Susilo Saefullah (EBTIDA': Jurnal Pendidikan Dasar Islam, 2026)
This finding is driven by the importance of moral-based education in addressing issues of moral decline in the context of globalization, particularly at the Madrasah Ibtidaiyah (Islamic elementary school) level. This study aims to analyze teachers' perspectives on moral-based education and the role of the educational environment in supporting the learning process. This study uses a descriptive qualitative methodology. Data were collected through observation, interviews, and documentation with Madrasah teachers at MI Al-Manar, Telukjambe Timur, Karawang. The Miles and Huberman model was used for data analysis, which included data reduction, data presentation, and conclusion formulation. The findings indicate that teachers view moral-based education as the main foundation in the educational process, where success is assessed not only through academic achievement but also from the behavior and morals of students. In addition, the educational environment, including the physical environment of the madrasah, family, and community, contributes significantly to the development of students' morals, although obstacles remain such as limited facilities and infrastructure and low parental involvement. Therefore, collaboration between various stakeholders is crucial in supporting the optimization of moral-based education in Madrasah Ibtidaiyah.